Analysis of characteristics of the photonuclear reactions with charged particles in output channel using EMPIRE II and TALYS codes - Bezshyyko, O.A.; Golinka-Bezshyyko, L.O.; Kadenko, I.M.; Lymanets, A.O. (Вопросы атомной науки и техники, 2007)
Contribution of various photonuclear reaction channels for deriving Giant Dipole Resonance (GDR) parameters is considered. It is shown that output channels with emission of charged particles are very important for some nuclei. GDR parameters for nuclei ⁶⁰Ni, ⁶³Cu, ⁶⁴Zn are evaluated taking into account all photonuclear reaction output channels. EMPIRE II and TALYS codes have been used for calculations. Розглядається вклад різних каналів фотоядерних реакцій для отримання параметрів гігантського дипольного резонансу (ГДР). Відзначається, що канали із випромінюванням заряджених частинок є дуже важливими для деяких ядер. Параметри ГДР для ядер ⁶⁰Ni, ⁶³Cu, ⁶⁴Zn оцінюються із урахуванням усіх вихідних каналів фотоядерних реакцій. Для теоретичних розрахунків використовуються коди EMPIRE II і TALYS. Рассматривается вклад различных каналов фотоядерных реакций для получения параметров гигантского дипольного резонанса (ГДР). Отмечается, что канал с излучением заряженных частиц является очень важным для некоторых ядер. Параметры ГДР для ядер ⁶⁰Ni, ⁶³Cu, ⁶⁴Zn оцениваются с учетом всех выходных каналов фотоядерных реакций. Для теоретических расчетов используются коды EMPIRE II и TALYS.